Kajian terhadap Antusiasme Siswa dalam Mengikuti Pembelajaran Pendidikan Jasmani di SMAN 1 Simo - Hartono, Muhammad Bagus Bimo; Dwijayanti, Karlina (SPRINTER: Jurnal Ilmu Olahraga, 2024)
Physical education has a strategic role in creating individuals who are not only physically healthy, but also able to face life's challenges with a strong mentality and good character. However, students' enthusiasm for participating in physical education lessons is often a concern in efforts to increase participation and learning outcomes. This research aims to determine students' enthusiasm for participating in physical education at the high school level. The survey was conducted on 100 students at SMA N 1 Simo using a questionnaire developed based on related literature and discussions with physical education experts. The questionnaire completed by students aims to measure aspects such as students' perceptions about the importance of physical health, fitness, skills acquired, as well as factors that influence students' enthusiasm in participating in physical education activities. The results of student data analysis show that the enthusiasm of SMA N 1 Simo students in participating in educational learning achieved good results with a percentage of 45.37%. These findings can provide a more in-depth picture of how to increase students' enthusiasm and effectiveness in participating in physical education learning in high school.